Ultrafast x-ray diffraction using a streak-camera detector in averaging mode. - Larsson, J; Chang, Z; Judd, E; Schuck, P; Falcone, R; Heimann, P; Padmore, H; Kapteyn, H; Bucksbaum, P; Murnane, M; Lee, R; Machacek, A; et al. (1997)
We demonstrate an apparatus for measuring time-dependent x-ray diffraction. X-ray pulses from a synchrotron are diffracted by a pair of Si(111) crystals and detected with an x-ray streak camera that has single-shot resolution of better than 1 ps. The streak camera is driven by a photoconductive switch, which is triggered by 100-fs laser pulses at a repetition rate of 1 kHz. The laser and the streak camera are synchronized with the synchrotron pulses. In the averaging mode, trigger jitter results in 2-ps temporal resolution. We measured the duration of 5-keV pulses from the Advanced Light Source synchrotron to be 70ps.